Proyecto de Factibilidad para la creación del complejo turístico “LA VICTORIA” ubicado en la parroquia La Victoria del cantón Pujilí. - Velásquez Quezada, Gina Alejandra (2021)
The general objective of this development work was to design a Feasibility Project for the creation of the tourist complex "LA VICTORIA" located in the La Victoria parish of the Pujilí canton, and as specific objectives to carry out a market study that identifies the unsatisfied demand and analysis of the prices of the services to be offered, preparing a technical study that defines the size, location, engineering and administrative proposal of the service and carrying out the financial analysis and evaluation identifying investments, costs, expenses and the economic viability of the project. A descriptive quantitative approach was applied, the research method used is deductive, the technique applied was the survey and the questionnaire as an instrument, for all this a population of 80,670 tourists who visited Pujilí in 2019 was considered, obtaining a sample of 382 individuals. This study determined an unsatisfied demand of 15,358 places per year for the year 2021, so it is intended to cover this demand by 71.30%. The services to be offered are accommodation, food, reception, recreation and local tourism, with an investment of 399,610.50 dollars, which will be contributed by four partners equally. The financial evaluation showed a net present value of $129,342.39 dollars, an internal rate of return of 23.80%, higher than the opportunity rate of 11.70% and a recovery period of 2 years 9 months and 18 days demonstrating the feasibility of this project.